Bed net ownership, use and perceptions among women seeking antenatal care in Kinshasa, Democratic Republic of the Congo (DRC): Opportunities for improved maternal and child health - Tabala Martine; Duvall Sandra; Nku David; Taylor Eboni; Pettifor Audrey; Meshnick Steve; Behets Frieda (BMC, 2008)
Abstract Background To describe malaria knowledge, attitudes toward malaria and bed net use, levels of ownership and use of bed nets, and factors associated with ownership and use among pregnant women attending their first antenatal care (ANC) visit in Kinshasa, DRC. Methods Women attending their first ANC visit at one maternity in Kinshasa were recruited to take part in a study where they were given free insecticide treated bed nets (ITNs) and then followed up at delivery and 6 months post delivery to assess ITN use. This study describes the baseline levels of bed net ownership and use, attitudes towards net use and factors associated with net use Results Among 351 women interviewed at baseline, 115 (33%) already owned a bed net and 86 (25%) reported to have slept under the net the previous night. Cost was reported as the reason for not owning a net by 48% of the 236 women who did not own one. In multivariable analyses, women who had secondary school or higher education were 3.4 times more likely to own a net (95% CI 1.6-7.3) and 2.8 times more likely to have used a net (95% CI 1.3-6.0) compared to women with less education Conclusion Distribution of ITNs in antenatal clinics in this setting is needed and feasible. The potential for ITN use by this target population is high.